Constraints And Solutions In Evaluating Competency-Based PJOK Learning In Secondary Schools - Rindawan, Rindawan; Muhsan, Muhsan; Sanrijaya, Niqsanding (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to identify obstacles and solutions in the implementation of competency-based learning evaluation of Physical Education, Sports and Health (PJOK) in secondary schools. The research method used is descriptive qualitative approach with data collection techniques through interviews, observations, and documentation studies. The results showed that there are several significant obstacles in evaluating PJOK learning, including limited facilities and infrastructure, lack of teacher understanding of the concept of competency-based evaluation, inflexible schedule preparation, and evaluation methods that are not in accordance with student needs. These constraints have a direct impact on students' learning experience, such as decreased motivation, increased stress levels, and the perception that the evaluation does not reflect their overall abilities. As a solution, this research proposes several steps, including the provision of special training for PJOK teachers regarding competency-based evaluation, optimization of facilities and infrastructure through collaboration with related parties, preparation of a more flexible schedule, and increased collaboration between teachers in the preparation of fairer and more comprehensive evaluation methods. The implementation of these solutions is expected to overcome the obstacles faced and increase the effectiveness of the evaluation of PJOK learning in secondary schools. Thus, competency-based evaluation can provide a more complete picture of students' abilities, including physical, cognitive, and affective aspects, and support the achievement of PJOK learning objectives optimally.